Relationship of Resilience, Anxiety and Injuries in Footballers: Structural Equations Analysis - Cofre-Bolados, C (Public Library of Science, 2018)
Resilience is a psychological characteristic which enhances personal assets and protects individuals from potential negative effects of various stressors. While this topic has been considered in the separate context of sports injuries and anxiety states, these issues have rarely been considered together. The objective of this study is to analyse the association between motivation to overcome injuries in football and the state of anxiety caused by those injuries. One hundred and eighty-five footballers from Spain were analysed by way of the Connor-Davidson Resilience Scale, the State-Trait Anxiety Inventory questionnaires, and an injury self-registration sheet. Statistical analyses were performed using structural equations. Results showed a direct and positive relationship between the capacity to face up to injuries or potential injuries and to adapt successfully to them for injured footballers, especially when anxiety was considered as a transitory emotional state. In addition, this relationship was stronger in non-injured sportspersons because their resilience capacity was not being impaired by the experience of an injury. © 2018 Zurita-Ortega et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.